Investigating the simultaneous effect of age and temperature on the population dynamics of female tsetse flies - Elama Ameh, Josephine; Ochigbo, Josephine Elanma (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.